Efektivitas Evaluasi Menggunakan Penskoran Bentuk Pilihan Ganda pada Pembelajaran Akidah di SD IT Diana As Saffa Islamic Kota Lhokseumawe - Ulya, Nuratul; Wardhani, Nia (Pase: Journal of Contemporary Islamic Education, 2024)
Learning evaluation is a crucial component of education, including in aqidah (Islamic creed) learning, which emphasizes both conceptual and spiritual understanding. At SD IT Diana As Saffa Islamic, Lhokseumawe City, multiple-choice tests are the primary method used by teachers to assess students’ comprehension. This study employs a qualitative approach, utilizing a descriptive method and a field research design. Data were collected through observation, structured interviews with teachers and students, and documentation studies. Data analysis was conducted through reduction, presentation, and conclusion drawing based on the Miles et al. model. The results indicate that the multiple-choice evaluation is considered effective by teachers and positively received by students. Teachers adjust the difficulty level of questions according to grade level, and students feel supported by the post-evaluation discussions. However, challenges were identified in the scoring techniques, including the use of conventional scoring without considering question difficulty levels and the absence of standardized scoring guidelines. Multiple-choice evaluation offers advantages in terms of efficiency and objectivity, but it is not yet fully capable of measuring the depth of understanding and the values of aqidah. Teachers need training in item construction and valid, fair scoring techniques. They also need to adopt reflective and exploratory approaches to better support the holistic goals of Islamic education.